Surface treatments for biological, chemical and physical applications - Gürsoy, Mehmet; Karaman, Mustafa (Weinheim, Germany : Wiley-VCH, 2017)
A step-by-step guide to the topic with a mix of theory and practice in the fields of biology, chemistry and physics. Straightforward and well-structured, the first chapter introduces fundamental aspects of surface treatments, after which examples from nature are given. Subsequent chapters discuss various methods to surface modification, including chemical and physical approaches, followed by the characterization of the functionalized surfaces. Applications discussed include the lotus effect, diffusion barriers, enzyme immobilization and catalysis. Finally, the book concludes with a look at future technology advances. Throughout the text, tutorials and case studies are used for training purposes to grant a deeper understanding of the topic, resulting in an essential reference for students as well as for experienced engineers in R&D.
Surfaces in Nature / Mehmet Gürsoy, Mustafa Karaman -- Chemical and Physical Modification of Surfaces / Mustafa Karaman, Mehmet Gürsoy, Mahmut Kus, Faruk Ozel, Esma Yenel, Ozlem G Sahin, Hilal D Kivrak -- Surface Characterization Techniques / Gokhan Erdogan, Günnur Güler, Tugba Kilic, Duygu O Kilic, Beyhan Erdogan, Zahide Tosun, Hilal D Kivrak, Ugur Türkan, Fatih Ozcan, Mehmet Gürsoy, Mustafa Karaman -- Surface Modification of Polymeric Membranes for Various Separation Processes / Woei-Jye Lau, Chi-Siang Ong, Nik Abdul Hadi Md Nordin, Nur Aimie Abdullah Sani, Nadzirah Mohd Mokhtar, Rasoul Jamshidi Gohari, Daryoush Emadzadeh, Ahmad Fauzi Ismail -- Langmuir-Blodgett Films: Sensor and Biomedical Applications and Comparisons with the Layer-by-Layer Method / Epameinondas Leontidis -- Surface Modification of Biopolymer-Based Nanoforms and Their Biological Applications / Susana CM Fernandes -- Enzyme-Based Biosensors in Food Industry via Surface Modifications / Nilay Gazel, Huseyin B Yildiz -- Heterogeneous Catalysis from the Perspective of Surface Science / Aydin Cihanoglu, Diego Hernan Quinones-Murillo, Gizem Payer.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed November 30, 2016).
Keywords: Surface chemistry; Surface active agents; TECHNOLOGY & ENGINEERING / Materials Science / General; SCIENCE / Chemistry / Physical & Theoretical; Surface active agents; Surface chemistry; Electronic books